Spatiotemporal trends of atmospheric dryness during 1980–2021 in Yunnan, China - Qin, Haiqin; Tan, Yingying; Shen, Ting; Schaefer, Doug Allen; Chen, Huafang; Zhou, Shaoqi; Xu, Qiang; Zhu, Yingmo; Cheng, Jinxin; Zhao, Gaojuan; Xu, Jianchu (Frontiers in Forests and Global Change, 2024)
Understanding the spatiotemporal patterns and variations in vapor pressure deficit (VPD) is essential for effective water resource management in the face of climate change. VPD serves as a fundamental indicator of atmospheric dryness, directly impacting plant evapotranspiration rates, thereby affecting overall ecosystem functioning. This study investigated variations in VPD across five subregions and four ecological land types in Yunnan from 1980 to 2021. We found increasing trends in annual VPD that were larger during warmer spring and summer seasons. Among the subregions, the highland subtropical southern broadleaved evergreen forest ecoregion exhibited the largest drying trend (0.04 kPa / decade), while the subtropical (eastern) humid broadleaved evergreen forest ecoregion had the smallest drying trend (0.01 kPa / decade). Among the ecological barriers, the dry-hot valleys had significantly higher increases in VPD compared to other Yunnan regions. Increases in VPD from 1990s to 2000s in several regions of Yunnan exceeded atmospheric drying trends reported elsewhere. Additionally, we documented smaller VPD declines at higher elevations. Across different ecological land types, Shrubland exhibited the largest VPD trend (0.07 kPa / decade), while Forest displayed the smallest (0.03 kPa / decade). Decreased relative humidity through time explained 65% of the increase in VPD in Yunnan, while increasing temperatures accounted for 25%. These findings provide valuable insights into climatic dynamics of Yunnan, with implications for ecological, hydrological, and atmospheric studies.